2021
DOI: 10.1016/j.psym.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Buprenorphine Micro-dosing Induction in a Patient on Methadone Treatment: A Case Report

Abstract: Introduction Buprenorphine in the treatment of opioid use disorder (OUD) has several benefits including better long-term treatment adherence (1) and is a safer option for many patients due to buprenorphine’s limited potential to cause respiratory depression (4). In comparison to standard buprenorphine induction, induction via micro-dosing does not require a period of withdrawal and dramatically shortens the time required to complete induction. Prior micro-dosing protocols using sublingual (SL) (7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 22 publications
(24 reference statements)
0
26
0
Order By: Relevance
“…A total of 20 reports provided data relevant to our research question (Table 1 ) [ 44 – 52 , 65 78 ]. One was an open-label study, ten were case series, and nine were individual case reports.…”
Section: Review Of Microdoinduction Reportsmentioning
confidence: 99%
“…A total of 20 reports provided data relevant to our research question (Table 1 ) [ 44 – 52 , 65 78 ]. One was an open-label study, ten were case series, and nine were individual case reports.…”
Section: Review Of Microdoinduction Reportsmentioning
confidence: 99%
“…There are also some novel techniques including microinduction of buprenorphine ( Payler, 2016 ; Crane et al, 2020 ), use of transdermal buprenorphine patch ( Raheemullah and Lembke, 2019 ), or other “bridge” techniques (Fentanyl, hydromorphone, slow release morphine, or others), or the concomitant administration of lofexidine, analgesics, or psychotropic drugs to reduce withdrawal symptoms. The possible advantage of microdosing technique is to minimize the risk for precipitated withdrawal and to improve patient comfort.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada slow release morphine was used for transferring patients on methadone to buprenorphine ( Ghosh et al, 2019a ). Finally, Crane et al (2020) reported the case of a 62-year-old patient on chronic methadone 80 mg daily referred to an emergency department with opioid overdose. He received 0.4 mg IV naloxone twice, then a naloxone infusion at 0.06 mg/h was started and an IV buprenorphine microdosing induction was initiated without interruption of methadone treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategy of microdosing was originally published by a group from Bern, Switzerland, and hence is called the "Bernese" microdosing strategy [60•]. Within the last 3 years, multiple groups have reported success with this approach in converting patients to buprenorphine [61][62][63][64][65][66]. The potent opioid is continued until SL buprenorphine doses are 8-12 mg. Buprenorphine gradually blocks the potent opioid access to MOR and becomes the primary analgesic or maintenance opioid.…”
Section: Methods For Rotating To Buprenorphinementioning
confidence: 99%